2018
DOI: 10.1146/annurev-arplant-042817-040615
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Ways to Invent the Sexes: Theoretical and Observed Paths to Dioecy in Plants

Abstract: Dioecy, the presence of male and female flowers on separate individuals, is both widespread and uncommon within flowering plants, with only a few percent of dioecious species spread across most major phylogenetic taxa. It is therefore safe to assume that dioecy evolved independently in these different groups, which allows us to ask questions regarding the molecular and developmental mechanisms underlying these independent transitions to dioecy. We start this review by examining the problem from the standpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 97 publications
(134 reference statements)
3
93
0
Order By: Relevance
“…The authors identified a Type C response regulator ( Shy Girl, SyGI ) on the Y chromosome that was associated with maleness. Overexpression of this gene in Arabidopsis and Nicotiana tabacum caused suppression of carpel development, supporting its potential role as a suppressor of female function [14]. This work has some interesting parallels with the results reported here for Salix and Populus .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The authors identified a Type C response regulator ( Shy Girl, SyGI ) on the Y chromosome that was associated with maleness. Overexpression of this gene in Arabidopsis and Nicotiana tabacum caused suppression of carpel development, supporting its potential role as a suppressor of female function [14]. This work has some interesting parallels with the results reported here for Salix and Populus .…”
Section: Discussionsupporting
confidence: 83%
“…However, RR9 and SyGI are clearly not orthologous and likely perform different roles in cytokinin signal transduction. This supports the view that there are numerous ways to achieve separate sexes in plants, and it is likely that a myriad of mechanisms underlie the hundreds of independent occurrences of dioecy in the angiosperms [51], even if a relatively small number of pathways are involved [11, 14].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The origin and evolution of dioecy (separate sexes) has long been one of the most fascinating topics for biologists (Henry et al, 2018; Feng et al , 2020). The presence of dioecy ensures outcrossing and optimal allocation of reproductive resources for male and female sexual function, thereby providing them with certain advantages in fertility, survival and evolution (Bawa, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence todate supports several models, including a two-locus model (Westergaard, 1958) in Fragaria virginiana (Spigler et al, 2008), Silene latifolia (Fujita et al, 2011) and Actinidia spp. (Akagi et al, 2019), a single switch gene in Diospyros lotus (Akagi et al, 2014) and others (Renner, 2016;Pannell, 2017;Henry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%